1998
DOI: 10.1021/ma970065v
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Ionic Aggregates in Carboxylato- and Sulfonato-Telechelic Polyisoprenes As Investigated by Small-Angle X-ray Scattering

Abstract: Twenty seven samples of carboxylato- and sulfonato-telechelic polyisoprenes associated with various cations (Na, K, Rb, Cs, Mg, Ca, Sr, and Ba) have been investigated by small-angle X-ray scattering. The Bragg spacing characteristic of the ionic peak is directly proportional to the root-mean-square end-to-end distance (r rms) of the polyisoprene chain. In the series of sulfonato-telechelic polyisoprenes, the Bragg spacing is approximately equal to r rms, whereas in the series of carboxylato-telechelic polyisop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
5
11
0
Order By: Relevance
“…Stadler et al also observed a shifting of the SAXS maxima for urazoylbenzoic acid functionalized polybutadiene to a higher q for higher levels of functionality (lower molecular weight between functional groups) 23. Jérôme et al correlated Bragg spacing with molecular weight ( d ∼ $\overline M _{{\rm n},}$ 0.5 ) for telechelic polyisoprene ionomers, and similar trends with molecular weight were apparent for the present UPy functionalized polymers 25…”
Section: Resultssupporting
confidence: 55%
“…Stadler et al also observed a shifting of the SAXS maxima for urazoylbenzoic acid functionalized polybutadiene to a higher q for higher levels of functionality (lower molecular weight between functional groups) 23. Jérôme et al correlated Bragg spacing with molecular weight ( d ∼ $\overline M _{{\rm n},}$ 0.5 ) for telechelic polyisoprene ionomers, and similar trends with molecular weight were apparent for the present UPy functionalized polymers 25…”
Section: Resultssupporting
confidence: 55%
“…The greater the molecular weight, the smaller the s position and the intensity of this peak. This latter observation qualitatively agrees with previous results in the case of sulfonatopolyisoprenes neutralized with a metallic cation X (monovalent or divalent) where dw is proportional to the square root of the molecular weight (Mn) 1/2 (Sobry, Fontaine, Ledent, Foucart & Jrr6me, 1998). In other words, the characteristic distance between the aggregates increases with the polymer chain length.…”
Section: /Swsupporting
confidence: 92%
“…Sobry et al observed a similar trend of interdomain spacing with molecular weight for telechelically functionalized ionomers, finding that the interdomain spacing was proportional to the root-mean-square end to end distance (10).…”
Section: Saxs Characterizationmentioning
confidence: 69%